The Relationship of Spirituality Level with Motivation to Heal Critical Patients at Tgk Chik Hospital in Tiro Sigli - Risna Risna; Muhammad Iqbal (Budapest International Research and Critics University, 2021)
Several studies have shown that low spirituality in critical patients results in reduced expectations, strength and motivation to face the critical conditions they face. The purpose of this study was to determine the relationship between spirituality level and motivation to recover in critical patients at Tgk Chik Hospital in Tiro Sigli. This type of research is descriptive research. The subjects of this study were 30 critical patients who were selected by accidental sampling. The variables in this study were spirituality as the independent variable and the dependent variable was the patient's motivation to recover. Data collection instruments in the study consisted of a demographic and characteristic data questionnaire, a Spirituality questionnaire and a patient recovery motivation questionnaire using the Acceptance Illness Scale (AIS). The relationship between spirituality and patient motivation to recover was analyzed using the Spearman Rank (Rho) test. The results showed that almost half (47.1%) of critical patients had moderate spirituality and low spirituality (29%); almost half (47.1%) experienced moderate and high motivation to recover (32.1%). There is a relationship between spirituality and motivation to heal patients (p = 0.002), where patients who have high spirituality have high motivation to recover.